Amlodipine overdose with hypotension and noncardiogenic pulmonary edema - Hirachan, Anish; Baral, Sushil; Shareef, Miqdaadh; Rijal, Rishikesh; Tibrewala, Laxman (Nepalese Heart Journal, 2016)
Amlodipine overdose can be a life threatening situation when it is manifested as noncardiogenic pulmonary edema. Treatment remains challenging when it is complicated with refractory hypotension and pulmonary edema. Here we describe a 23 year old female with history of ingestion of 45 tabs (5mg) of amlodipine as a suicidal intent and presented within 36 hours to the hospital. High flow oxygen, IV fluids, calcium gluconate infusion and antibiotics were used for the management. After 7 days of hospital stay, patient was discharged with full recovery.   Nepalese Heart Journal 2016; 13(1): 27-29